How Brain Infarction Links With the Microbiota–Gut–Brain Axis: Hints From Studies Focusing on the Risk Factors for Ischemic Stroke - Liu, Yunpeng; Dong, Jing; Zhang, Ziqing; Liu, Yiqi; Wang, Yang (Frontiers in Neuroscience, 2022)
Ischemic stroke (IS) is among the top prevalent neurologic disorders globally today. Risk factors such as hypertension, diabetes, and aging, contribute to the development of IS, and patients with these risk factors face heavier therapeutic burden and worse prognosis. Microbiota–gut–brain axis describes the crosstalk between the gut flora, intestine, and center nervous system, which conduct homeostatic effects through the bacterial metabolites, the regulation of immune activity, also the contact with enteric nerve ends and vagus nerve. Nowadays, more studies have paid attention to the important roles that microbiota–gut–brain axis played in the risk factors of IS. In the current article, we will review the recent works focusing on the bi-directional impacts of gut dysbiosis and the pathogenic process of IS-related risk factors, for the purpose to summarize some novel findings in this area, and try to understand how probiotics could limit the development of IS via different strategies.